The Level of Educational Leaders Commitment to the Organizational Intelligence Dimensions in the Saudi Educational Institutions from the Perspective of Teaching Board Members and the Educational Leaders - Alaiwa, Khawla Husain Taha (European Scientific Journal, ESJ, 2018)
The current study aims to identify the level of educational leaders commitment to the organizational intelligence in the Saudi educational institutions from the perspective of the teaching board members and the educational leaders, also identifying the organizational intelligence dimensions and its domains. To achieve the study objectives, the researcher applied the descriptive analytical approach. The study has been applied over a random sample of educational leaders and teaching board members in the Faculty of Education of Ha’il University. The study sample included (102) members. The study concluded that there is a high level of commitment from the educational leaders to the organizational intelligence. In the end, the researcher recommended the need to continue following a methodology based on the exploitation of human resources in the institution.